2005
DOI: 10.1051/lait:2005010
|View full text |Cite
|
Sign up to set email alerts
|

Factors moderating Listeria monocytogenes growth in raw milk and in soft cheese made from raw milk

Abstract: -Listeria monocytogenes is a foodborne pathogenic bacterium sometimes found in raw milk. Raw milk contains natural bacterial inhibitors such as the lactoperoxidase system (LPS) and specific microflora. Six strains of L. monocytogenes isolated from raw milk in 1995 and 1996 in Normandy (France) were tested. The aim of the first part of this work was to evaluate the inhibitory effect of LPS on L. monocytogenes in milk. Kept at 15 °C for 65 h, in static conditions, populations of L. monocytogenes in pasteurized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Our results in the cores of consortium cheeses differed from those of Gay and Amgar (2005) who observed a higher L. monocytogenes growth rate in pasteurized milk stored at 15 C than at 9 C. Back et al (1993) also reported a lower growth rate at 8 C than at 15 C in Camembert and soft cheeses. But these data from the literature are in agreement with those obtained in our control cheeses.…”
Section: Listeria Countscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results in the cores of consortium cheeses differed from those of Gay and Amgar (2005) who observed a higher L. monocytogenes growth rate in pasteurized milk stored at 15 C than at 9 C. Back et al (1993) also reported a lower growth rate at 8 C than at 15 C in Camembert and soft cheeses. But these data from the literature are in agreement with those obtained in our control cheeses.…”
Section: Listeria Countscontrasting
confidence: 99%
“…Such inhibition by a complex consortium has also been observed in raw milk versus pasteurised (Gay & Amgar, 2005), in the cores of PDO Saint-Nectaire cheeses (Millet et al, 2006;Saubusse et al, 2007) and also in their rinds (Retureau et al, 2010) and in the rinds of smear cheeses (Maoz et al, 2003;Mayr et al, 2004;Roth et al, 2010).…”
Section: Listeria Countsmentioning
confidence: 71%
See 1 more Smart Citation
“…Camembert is the most common soft cheese studied regarding the growth of L. monocytogenes (Back et al . ; Gay and Amgar ; Linton et al . ; Kapetanakou et al .…”
Section: Survival Of Listeria Monocytogenes In Cheesementioning
confidence: 99%
“…The natural flora of raw milk and raw milk cheeses may also contribute to food biopreservation (Callon, Saubusse, Didienne, Buchin, & Montel, 2011;Eppert, Valdes-Stauber, Gotz, Busse, & Scherer, 1997;Gay & Amgar, 2005;Imran, Desmasures, & Vernoux, 2010;Retureau, Callon, Didienne, & Montel, 2010). Thus, the microbial diversity of raw milk directly impacts the quality of dairy products, including raw milk cheeses (natural microflora), but it also attracts interest as a source of indigenous cheese starters.…”
Section: Introductionmentioning
confidence: 99%